2020
DOI: 10.1016/j.freeradbiomed.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, telomeres and cellular senescence: What non-drug interventions might break the link?

Jorge D. Erusalimsky

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 108 publications
1
13
0
Order By: Relevance
“…Furthermore, telomere oxidative lesions are less efficiently repaired because of the telomere heterochromatin state, suggesting that telomeres are most vulnerable to oxidative damage (Smith, 2018;Coluzzi et al, 2019;Singh et al, 2019). Accordingly, oxidative stress is considered to be the main cause of telomere shortening (Erusalimsky, 2020). Cigarette smoke, a source of exogenous pro-oxidants, has been confirmed to be associated with increased oxidative stress in the ovary (Sobinoff et al, 2013;Mai et al, 2014;Kim et al, 2018;.…”
Section: Oxidative Stress and Telomeres In The Ovariesmentioning
confidence: 99%
“…Furthermore, telomere oxidative lesions are less efficiently repaired because of the telomere heterochromatin state, suggesting that telomeres are most vulnerable to oxidative damage (Smith, 2018;Coluzzi et al, 2019;Singh et al, 2019). Accordingly, oxidative stress is considered to be the main cause of telomere shortening (Erusalimsky, 2020). Cigarette smoke, a source of exogenous pro-oxidants, has been confirmed to be associated with increased oxidative stress in the ovary (Sobinoff et al, 2013;Mai et al, 2014;Kim et al, 2018;.…”
Section: Oxidative Stress and Telomeres In The Ovariesmentioning
confidence: 99%
“…Further investigations focused on the missing links between oxidative stress and telomere length. Initially, research was based on in vitro studies using cultured cells that demonstrated the association between oxidative stress inductors and premature senescence [8]. Epel et al discovered the existence of the association between oxidative stress and accelerated telomeres shortening in humans in 2004 [9].…”
Section: Psychological Stress and Agingmentioning
confidence: 99%
“…The ability to slow telomere shortening and activate telomerase has been shown for many natural compounds ( Table 2 ). Most of them protect telomeric DNA by reducing damage by genotoxic agents, but their effect is small [ 81 , 675 ]. A promising strategy could also be coordinating the organization and stability of telomeres, for example, by targeting guanine-quadruplexes.…”
Section: Pharmacological Interventions Protecting Genomementioning
confidence: 99%